2022
DOI: 10.3389/fmed.2022.799156
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Various Drug Interventions to Prevent Etomidate-Induced Myoclonus: A Bayesian Network Meta-Analysis

Abstract: BackgroundMyoclonic movement is a very common but undesirable phenomenon during the induction of general anesthesia using etomidate. Such movement may cause unnecessary problems. Currently, there is an increasing number of drugs for preventing etomidate-induced myoclonus (EM). However, direct comparisons of various drugs are lacking, and this interferes with clinical decision-making. Our network meta-analysis (NMA) aimed to compare the efficacy of different drugs for the prevention of moderate-to-severe genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
5
0
1
Order By: Relevance
“…According to them, both were safe and effective for making induction of anesthesia safer by preventing the myoclonus associated with etomidate. 16 Similarly, Hüter et al 17 found the same results using low dose midazolam (0.015mg/kg) 3 minutes before etomidate induction in elective cardioversion patients. Forty patients were included in their study, and all belonged to ASA-III & IV.…”
Section: Discussionmentioning
confidence: 76%
“…According to them, both were safe and effective for making induction of anesthesia safer by preventing the myoclonus associated with etomidate. 16 Similarly, Hüter et al 17 found the same results using low dose midazolam (0.015mg/kg) 3 minutes before etomidate induction in elective cardioversion patients. Forty patients were included in their study, and all belonged to ASA-III & IV.…”
Section: Discussionmentioning
confidence: 76%
“…The various agents that have been employed to suppress this effect include midazolam,[ 6 7 ] fentanyl,[ 13 ] remifentanil,[ 14 ] magnesium sulphate,[ 10 15 ] lignocaine,[ 16 ] butorphanol,[ 3 9 17 18 ] dexmedetomidine,[ 1 2 8 19 20 21 22 ] thiopental[ 21 ] and sub-hypnotic doses of etomidate. [ 23 ] Dexmedetomidine has the edge over the other agents, given its diverse actions, including conscious sedation, analgesia and preventing haemodynamic response to laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 99%
“…[52] zwracają jednak uwagę na konieczność zachowania znacznej ostrożności w rutynowym dołączaniu remifentanylu do znieczulenia barbituranowego, gdyż nie wpływa to na długoterminowe odsetki remisji i nawrotów, a wiąże się z częstszym ryzykiem działań niepożądanych, takich jak nudności, zawroty czy bóle głowy. Według najnowszej metaanalizy sieciowej zastosowanie remifentanylu wydaje się natomiast najlepszą opcją w zapobieganiu miokloniom indukowanym przez etomidat, co może mieć szczególne znaczenie u chorych z wysokim wyjściowym stężeniem potasu przy jednoczesnym zastosowaniu sukcynylocholiny, jako że zarówno mioklonie, jak i sukcynylocholina powodują silne przesunięcie jonów potasu na zewnątrz komórki mięśniowej [53].…”
Section: Szczególne Zastosowania śRodków Anestezjologicznychunclassified